Fuel consumption in an air blower for agricultural use under different operating conditions - Robson L. da Silva (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Evaluation of fuel consumption in internal combustion engines (ICE) of agricultural machinery and equipment is important in determining the performance under various operating conditions, especially when using biofuels. This study consisted of experimental evaluation of the gasoline (petrol)/ethanol consumption in a two-stroke 1-cylinder ICE, Otto cycle, functioning as an air blower for agriculture and related applications. A methodology for tests of non-automotive ICE, based on ABNT/NBR technical standards, was considered. The presented results refer to operation with commercial and non-commercial fuel blends. Characteristic curves for the tested equipment are presented, identifying consumption conditions and trend in the whole operating range of angular speeds (RPM), for five fuel blends (gasoline/ethanol). For the operating conditions of minimum and maximum angular speeds, 20 and 30% ethanol blends had the highest and lowest fuel consumptions, respectively.